2021
DOI: 10.21037/atm-20-6796
|View full text |Cite
|
Sign up to set email alerts
|

High risk of pulmonary embolism in acute respiratory distress syndrome related to COVID-19: an observational controlled-cohort study

Abstract: Background: COVID-19 may induce endovascular injury of pulmonary vessels and could be associated with increased risk of pulmonary embolism. The main objective was to compare the incidence of pulmonary embolism in patients with acute respiratory distress syndrome (ARDS) related to COVID-19 versus patients with pulmonary ARDS unrelated to COVID-19.Methods: This is an observational controlled-cohort study performed at a single center of a university teaching hospital in France. The incidence of pulmonary embolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…9 Clinically, several symptoms or biomarkers, such as ARDS, hyperferritinemia, and elevated sIL-2 levels, are known risk factors for thrombosis or coagulopathy caused by COVID-19. 10,11 It has been reported that arterial thrombosis has been observed in 4.4% of severe COVID-19 patients. 12 The anatomical distribution of these arterial thromboses was broad and they can be observed in the arteries, such as the limb arteries, cerebral arteries, and the great vessels (aorta, common iliac, common carotid, brachiocephalic trunk, coronary arteries, and superior mesenteric artery).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Clinically, several symptoms or biomarkers, such as ARDS, hyperferritinemia, and elevated sIL-2 levels, are known risk factors for thrombosis or coagulopathy caused by COVID-19. 10,11 It has been reported that arterial thrombosis has been observed in 4.4% of severe COVID-19 patients. 12 The anatomical distribution of these arterial thromboses was broad and they can be observed in the arteries, such as the limb arteries, cerebral arteries, and the great vessels (aorta, common iliac, common carotid, brachiocephalic trunk, coronary arteries, and superior mesenteric artery).…”
Section: Discussionmentioning
confidence: 99%
“…9 Clinically, several symptoms or biomarkers, such as ARDS, hyperferritinemia, and elevated sIL-2 levels, are known risk factors for thrombosis or coagulopathy caused by COVID-19. 10,11…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, LUS can accurately diagnose and quantify pleural effusions which may be more difficult on chest x-ray [ 72 ]. Finally, pulmonary embolism is a difficult-to-diagnose complication with a high incidence during ARDS (between 5 and 10%), and requires CT with pulmonary angiography as part of the diagnostic work-up in worsening ARDS patients [ 73 ].…”
Section: Identifying Complications Of Ardsmentioning
confidence: 99%